2022
DOI: 10.1037/pha0000492
|View full text |Cite
|
Sign up to set email alerts
|

A genetic association study of tobacco withdrawal endophenotypes in African Americans.

Abstract: Genome-wide association (GWA) genetic epidemiology research has identified several variants modestly associated with brief self-report smoking measures, predominately in European Americans. GWA research has not applied intensive laboratory-based measures of smoking endophenotypes in African Americans-a population with disproportionately low quit smoking rates and high tobacco-related disease risk. This genetic epidemiology study of non-Hispanic African Americans tested associations of 89 genetic variants ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Participants were African American nontreatment seeking individuals who smoked cigarettes daily ( N = 344) recruited from Los Angeles, CA, United States during 2013−2017 via advertisements announcing a study on reasons people smoke cigarettes (Leventhal, Conti, et al, 2022). Inclusion criteria for the study were: (a) 18 years of age or older; (b) self-reported non-Hispanic African American; (c) daily cigarette smoking for ≥2 years; (d) currently smoking ≥10 cigarettes per day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were African American nontreatment seeking individuals who smoked cigarettes daily ( N = 344) recruited from Los Angeles, CA, United States during 2013−2017 via advertisements announcing a study on reasons people smoke cigarettes (Leventhal, Conti, et al, 2022). Inclusion criteria for the study were: (a) 18 years of age or older; (b) self-reported non-Hispanic African American; (c) daily cigarette smoking for ≥2 years; (d) currently smoking ≥10 cigarettes per day.…”
Section: Methodsmentioning
confidence: 99%
“…The present article reports results of a tack-on experiment to a parent study on individual differences in tobacco withdrawal phenotypes in African American individuals (Leventhal, Conti, et al, 2022). We added the racial discrimination Stroop measure into the parent study protocol midstream into data collection.…”
Section: Data Source Sample Size Determinations and Availability Of S...mentioning
confidence: 99%